Simulation and modeling methodologies, technologies and applications : International Conference, SIMULTECH 2013 Reykjavík, Iceland, July 29--31, 2013, revised selected papers /: International Conference, SIMULTECH 2013 Reykjavík, Iceland, July 29--31, 2013, revised selected papers. ([2014]) - Unknown
No abstract available